Duodenal GIST mass with big management challenges - Hassani, Mohammad; Tavallaei, Mehdi; Parhizgar, Parynaz; Bakhshaei Shahrbababki, Peyman (Researcher Bulletin of Medical Sciences, 2023)
Introduction: Gastrointestinal stromal tumor (GIST) is a rare mesenchymal tumor of the gastrointestinal (GI) tract that usually occurs in the stomach and the small intestine, respectively. This tumor often occurs in people over the age of 40 years, especially in the fifth and sixth decades of life. The range of symptoms varies from asymptomatic to symptomatic depending on the size and location of the tumor. The standard diagnostic of this tumor is the pathological examination of tissue specimens. Also today, the main treatment for this tumor is surgery and resection of the tumor. Case Report: A 43-year-old woman presented with melena and a decrease in hemoglobin level to 4. The patient underwent upper and lower GI endoscopy, CT angiography, and EUS, which was reported a vascular lesion below the ampulla of vater. After laparotomy and Whipple procedure, pathology reported tumor as GIST. The patient was discharged from the hospital in good general condition. Conclusion: we suggest that patients presented with gastrointestinal bleeding and the presence of a lesion in the diagnostic modalities, GIST should always be considered as a differential diagnosis.